EXPRESSION OF RESISTANCE OF SOYBEAN TO THE POD SUCKING BUG RIPTORTUS LINEARIS F. (HEMIPTERA: COREIDAE) - Suharsono Suharsono; Liliek Sulistyowati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2012)
Factors involved in the mechanism of resistance of soybean to pod sucking bug R. linearis were identified using resistant soybean genotypes, IAC-100, and IAC-80-596-2 and the susceptible variety, Wilis as a check. The role of trichomes in resistance was assayed removing trihomes from the pod shell, and seed coat and the resistance was determined based on the number of stylet punctures made by the bug. Seed of IAC-100 and IAC-596-2 that had longer, denser trichomes, higher crude fiber content and suffered fewer stylet punctures than Wilis. This suggested that denser and longer trichomes interfered with stylet piercing of the pod shell. When the trichomes of IAC-100 and IAC-596-2 were removed these genotypes were more susceptible to insect feeding. In further studies, replacement of IAC-100 and IAC-596-2 seed with seed of Wilis in the pods of resistant genotypes resulted less stylet punctures on the Wilis seed. It was concluded that denser and longer trichomes on pods along with harder pod shells acts as a physical barrier in antixenosis resistance of soybean to the pod sucking bug. Therefore, IAC-100, and IAC-596-2 genotypes have good potential for used as resistant parents in a soybean breeding program. Keywords: resistance, pod characters, tri-chomes, antixenosis, pod stink bug